Gambaran Kedisiplinan Santri Taman Pendidikan Al-Quran di Masjid Al-Hidayah Kota Solok - Agustina Agustina; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the high learning result of santri that can be seen from the achievement of studying santri tahfidz Al-Quran at Al Hidayah Mosque of Solok City. This condition is influenced because of the discipline of students who are very good in following the teaching and learning process. The purpose of this study is to look at the discipline of santri from: 1) discipline of time, 2) discipline in obedience and obedience, 3) discipline in responsibility. The population is twenty-one persons and a sample of twenty-one people is assigned based on the sampling technique of the census. The data collecting technique uses questionnaire of data collection tool. Data analysis techniques use percentage calculations. The results showed that the discipline of santri was very good in terms of 1) time discipline, 2) discipline in obedience and compliance, 3) discipline in responsibility. In conclusion santri have a very good discipline. The discipline of the students affects the improvement of the students' learning outcomes and their learning achievement. This research advice for santri in order to improve self-discipline in daily life.Keywords: Discipline, TPA